Impact of Culture Medium on Cellular Interactions in in vitro Co-culture Systems - Vis, Michelle A. M.; Ito, Keita; Hofmann, Sandra (Frontiers in Bioengineering and Biotechnology, 2020)
Co-culturing of cells in in vitro tissue models is widely used to study how they interact with each other. These models serve to represent a variety of processes in the human body such as development, homeostasis, regeneration and disease. The success of a co-culture is dependent on a large number of factors which makes it a complex and ambiguous task. This review article addresses co-culturing challenges regarding the cell culture medium used in these models, in particular concerning medium composition, volume, and exchange. The effect of medium exchange on cells is often an overlooked topic but particularly important when cell communication via soluble factors and extracellular vesicles, the so-called cell secretome (CS) is being studied. Culture medium is regularly exchanged to supply new nutrients and to eliminate waste products produced by the cells. By removing medium, important CSs are also removed. After every medium change, the cells must thus restore their auto- and paracrine communication through these CSs. This review article will also discuss the possibility to integrate biosensors into co-cultures, in particular to provide real-time information regarding media composition. Overall, the manner in which culture medium is currently used will be re-evaluated. Provided examples will be on the subject of bone tissue engineering.